2009
DOI: 10.1124/dmd.109.028449
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of Haloperidol and Sila-Haloperidol: New Metabolic Pathways Resulting from Carbon/Silicon Exchange

Abstract: ABSTRACT:The neurotoxic side effects observed for the neuroleptic agent haloperidol have been associated with its pyridinium metabolite. In a previous study, a silicon analog of haloperidol (sila-haloperidol) was synthesized, which contains a silicon atom instead of the carbon atom in the 4-position of the piperidine ring. In the present study, the phase I metabolism of sila-haloperidol and haloperidol was studied in rat and human liver microsomes. The phase II metabolism was studied in rat, dog, and human hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…Authors have observed the pyridinium ion by both electrochemical oxidation and incubation in the presence of rat-liver microsomes. This cutting-edge approach using EC-MS led to the elimination of the pyridinium-ion metabolite by modifying the pyridinium ring with a silica atom [46]. In addition, they reported the use of the cyanide ion as a chemical-trapping agent of the carbocationic intermediate [16].…”
Section: Pyridinium Reactive Metabolitesmentioning
confidence: 99%
“…Authors have observed the pyridinium ion by both electrochemical oxidation and incubation in the presence of rat-liver microsomes. This cutting-edge approach using EC-MS led to the elimination of the pyridinium-ion metabolite by modifying the pyridinium ring with a silica atom [46]. In addition, they reported the use of the cyanide ion as a chemical-trapping agent of the carbocationic intermediate [16].…”
Section: Pyridinium Reactive Metabolitesmentioning
confidence: 99%
“…Indeed, the metabolism of sila-haloperidol ( 220 ) follows more conventional pathways associated with the piperidine moiety in which oxidative metabolism occurs adjacent to the N atom leading to dealkylation of the fluorophenyl-containing side chain to afford 225 and ring hydroxylation that produces 228 and 230 (Fig. 34 ) [ 334 ].
Fig.
…”
Section: Isosteres To Address Metabolism and Toxicitymentioning
confidence: 99%
“…Silicon‐linked heterocycles have long been recognized as carbon isosteres of numerous bioactive molecules since silicon has unique physicochemical properties . Considering the abundance of N ‐heterocyclic units embedded in pharmacophores and alkaloids, the synthesis of sila‐ N ‐heterocycles is of special interest in a broad areas of chemistry . While there were no catalytic procedures documented for synthesis of such azasilaheterocycles, Park and Chang group recently conceived a new transformation of N ‐aryl piperidines leading to polycyclic sila‐ N ‐heterocycles via cascade processes involving consecutive dehydrogenation, hydrosilylation, and dehydrogenative coupling with the N ‐tolyl C(sp 2 )—H bond mediated by a single catalyst B(C 6 F 5 ) 3 .…”
Section: Silylative Cascade Of N‐aryl Piperidinesmentioning
confidence: 99%